Preparation method of crystalline magnesium lithium silicate for nanoscale colorful stone-like paint

Through a simple preparation method, crystalline magnesium silicate for nano-scale colorful imitation stone paint with high dispersion, thickening and light transmittance is prepared through a simple preparation method, which solves the problems of complex process and high cost in the existing technology and realizes the demand for industrial production.

CN119797385APending Publication Date: 2025-04-11FUJIAN NIEN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510004439.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the process of preparing crystalline magnesium silicate for nano-grade colorful imitation stone paint is complex and costly, and cannot meet the needs of industrial production.

Method used

A simple preparation method is adopted, including mixing silicon-containing compounds, magnesium-containing compounds and lithium-containing compounds with water, and adjusting the pH to 9-11 at room temperature, and then adding modified polyquaternary ammonium salt under ultrasound, and reacting with specific temperature and time conditions to obtain crystalline lithium magnesium silicate.

Benefits of technology

This method can effectively improve the dispersion, thickening, compatibility and light transmittance of lithium magnesium silicate, reduce preparation costs, simplify process flow, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of hectorite preparation, in particular to a preparation method of crystalline magnesium lithium silicate for nanoscale colorful stone-like paint, which comprises the following steps: S1, adding a silicon-containing compound, a magnesium-containing compound and a lithium-containing compound into water, adjusting the pH to 9-11 by NaOH at normal temperature, and performing ultrasonic treatment to obtain a mixed solution; and S2, adding modified polyquaternium into the mixed solution obtained in the step S1, stirring for 30-60 minutes at the temperature of 40-50 DEG C, and then reacting at the temperature of 115-125 DEG C to obtain the crystalline magnesium lithium silicate. The preparation method of the crystalline lithium magnesium silicate for the nanoscale colorful stone-like paint is simple, the light transmittance is high, the thixotropy is good, and the crystalline lithium magnesium silicate has good compatibility with other substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hectorite preparation, and in particular to a method for preparing crystalline lithium magnesium silicate for nano-level colorful stone-imitation paint. Background Art

[0002] Lithium magnesium silicate, also known as hectorite, laponite or hectorite, is an inorganic mineral with a 2:1 layered crystal structure, consisting of two layers of silicon-oxygen tetrahedrons sandwiching a layer of magnesium-oxygen octahedrons. The crystals of lithium magnesium silicate are irregular flakes, with a length and width of about 0.3-2.5μm and a thickness of about 15-230nm. This structure enables lithium magnesium silicate crystals to be evenly dispersed in water, with excellent thickening, thixotropy, and adsorption properties, and is widely used in inks, cosmetics, medicine and other fields. The formation conditions of natural lithium magnesium silicate are relatively harsh and it is relatively scarce in nature. In order to meet the needs of industrialization, it must rely on artificial synthesis, but there are still some defects in the current preparation method. The prepared lithium magnesium silicate has certain defects and cannot be effectively used.

[0003] Patent CN106946263B discloses a high-temperature solid-phase synthesis method for easily dispersible lithium magnesium silicate with high light transmittance. The synthesis method comprises the following process steps: first, sodium montmorillonite with a purity of not less than 95% is calcined at 150-200°C for 0.5-1.5h, then cooled to room temperature and lithium salt, sodium salt and magnesium salt are added, mixed evenly, and then calcined at 250-400°C for 2-3h, cooled to room temperature and discharged. The invention uses montmorillonite as the starting material and produces lithium magnesium silicate through a high-temperature solid-phase process with excellent light transmittance, hydration dispersion speed and thickening properties, but the invention requires two high-temperature calcinations, and the process is complicated.

[0004] Patent CN105800626B discloses a hydrothermal synthesis method for nano-scale lithium magnesium silicate with high light transmittance. The synthesis method is prepared by the following steps: first, montmorillonite is acidified and calcined; then, water-soluble lithium salt and water-soluble sodium salt are added to adjust the ratio, and finally, the mixture is reacted at 60-95°C for 1-3h, and finally, the mixture is fully dried at 110-150°C to obtain nano-scale lithium magnesium silicate with high light transmittance, excellent thickening and thixotropy, and strong adsorption capacity. The montmorillonite used in the invention is high-purity sodium-based montmorillonite, which increases the production cost to a certain extent.

[0005] Therefore, it is urgent to develop a method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint with simple preparation process and low cost. Summary of the invention

[0006] In order to overcome the above-mentioned deficiencies of the prior art, the present invention provides a crystalline lithium magnesium silicate for nano-scale colorful stone-like paint, which has a simple preparation process, high light transmittance, good thixotropy and good compatibility with other substances.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention provides a method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint, comprising the following steps:

[0009] S1. Add a silicon-containing compound, a magnesium-containing compound and a lithium-containing compound into water, adjust the pH to 9-11 with NaOH at room temperature, and perform ultrasound for 50-60 min at an ultrasound power of 80-100 W to obtain a mixed solution;

[0010] S2. Add modified polyquaternary ammonium salt to the mixed solution obtained in step S1, stir at 40-50° C. for 30-60 min, and then react at 115-125° C. to obtain crystalline lithium magnesium silicate.

[0011] In some embodiments, the silicon-containing compound is any one or more of sodium silicate, silicic acid, and silicon dioxide.

[0012] Preferably, the silicon-containing compound is sodium silicate.

[0013] In some embodiments, the magnesium-containing compound is any one or more of magnesium nitride, magnesium chloride, magnesium hydroxide, magnesium oxide, and magnesium acetate.

[0014] Preferably, the magnesium-containing compound is magnesium nitride.

[0015] In some embodiments, the lithium-containing compound is any one or more of lithium chloride, lithium acetate, and lithium carbonate.

[0016] Preferably, the lithium-containing compound is lithium chloride.

[0017] The preferred silicon-containing compound of the present invention is sodium silicate. The reactivity of silicon with magnesium is greater than that of silicon with lithium. + The presence of can reduce the conversion of Li-Mg into Si-Mg to a certain extent, ensuring the generation of Li-Mg-Si in the system. At the same time, the magnesium-containing compound is preferably magnesium nitride, which will generate ammonia in water. Ammonia is easily soluble in water and is alkaline in water, which can reduce the amount of sodium hydroxide added. In addition, the lithium-containing compound is preferably lithium chloride, which can increase the transmittance of the prepared lithium magnesium silicate.

[0018] In some embodiments, the mass ratio of the silicon-containing compound, the magnesium-containing compound, the lithium-containing compound and water is 1:(3-3.2):(16.7-17):(70-75).

[0019] The invention limits the mass ratio of silicon-containing, magnesium-containing and lithium-containing compounds so that the obtained lithium magnesium silicate has suitable dispersion viscosity, stability and dissolution rate, thereby increasing the application range.

[0020] In some embodiments, the method for preparing the modified polyquaternary ammonium salt comprises the following steps:

[0021] (1) Add 1H,1H-pentafluoropropanol, acrylic acid and concentrated sulfuric acid to dichloromethane, heat to 70-80° C., stir for 7-8 hours, and rotary evaporate to obtain the compound;

[0022] (2) adding the compound obtained in step (1), methacryloyloxyethyl trimethyl ammonium chloride and azobisisobutyronitrile to methanol, reacting at 60-70° C., detecting the number average molecular weight during the reaction, and obtaining a modified polyquaternary ammonium salt having a number average molecular weight of 680-940.

[0023] The invention modifies the polyquaternary ammonium salt and uses it for preparing an intercalation agent of lithium magnesium silicate, so that the lithium magnesium silicate has good viscosity, dispersion stability and thixotropic performance. The possible reason is that the presence of a large number of fluorine atoms can promote the generation of lithium magnesium silicate crystals, and the fluorine atoms have a large electronegativity, which can reduce the interfacial tension during use and improve the dispersion stability. In addition, after ultrasound treatment, a quaternary ammonium salt substance with a specific number average molecular weight is added as an intercalation agent, and the quaternary ammonium salt cation can enter the interlayer through ion exchange, so that the dispersibility and thickening of the lithium magnesium silicate are further improved, and the compatibility with other substances is increased, thereby improving the quality of the colorful imitation stone paint.

[0024] In some embodiments, the mass ratio of 1H,1H-pentafluoropropanol to acrylic acid is 1:(0.5-0.6).

[0025] In some embodiments, the mass ratio of the compound in step (2) to methacryloyloxyethyltrimethylammonium chloride is (0.4-0.6):1.

[0026] The present invention limits the mass ratio of 1H, 1H-pentafluoropropanol to acrylic acid so that the grafted double bonds of 1H, 1H-pentafluoropropanol react with methacryloyloxyethyltrimethylammonium chloride. In addition, the mass ratio of the compound to methacryloyloxyethyltrimethylammonium chloride is limited to avoid excessive fluorine atoms in the modified polyquaternary ammonium salt, thereby preventing the stability of the obtained lithium magnesium silicate from decreasing.

[0027] In some embodiments, the amount of the modified polyquaternary ammonium salt added in step S2 is 2-4% of the mass of the mixed solution.

[0028] The invention improves the dispersibility of lithium magnesium silicate by limiting the addition amount of modified polyquaternary ammonium salt, while avoiding the decrease of thixotropy caused by excessive quaternary ammonium salt.

[0029] In some embodiments, the reaction time in step S2 is 12-18 hours.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention adds modified polyquaternary ammonium salt after ultrasound, so that the modified polyquaternary ammonium salt can more easily enter the interlayer of lithium magnesium silicate, and the obtained lithium magnesium silicate has good dispersibility, thickening, compatibility and light transmittance.

[0032] 2. The present invention modifies the polyquaternary ammonium salt. The presence of a large number of fluorine atoms can promote the formation of lithium magnesium silicate crystals. At the same time, the fluorine atoms have a large electronegativity, which can reduce the interfacial tension during use and improve the dispersion stability. In addition, after ultrasound, a quaternary ammonium salt substance with a specific number average molecular weight is added as an intercalant, and the quaternary ammonium salt cation can enter the interlayer through ion exchange, which further improves the dispersibility and thickening of the lithium magnesium silicate, and also increases the compatibility with other substances, thereby improving the quality of the colorful imitation stone paint.

[0033] 3. The present invention limits the mass ratio of 1H, 1H-pentafluoropropanol to acrylic acid to allow the grafted double bonds of 1H, 1H-pentafluoropropanol to react with methacryloyloxyethyltrimethylammonium chloride. In addition, by limiting the mass ratio of the compound to methacryloyloxyethyltrimethylammonium chloride, the stability of the obtained lithium magnesium silicate is prevented from being decreased due to excessive fluorine atoms in the modified polyquaternary ammonium salt. DETAILED DESCRIPTION

[0034] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are only used to illustrate the present invention and are not intended to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0035] In order to facilitate those skilled in the art to implement the present invention, some raw materials and manufacturers of the embodiments and comparative examples are described as follows:

[0036] The compounds and related reagents used in the following examples and comparative examples can all be purchased from the market, and polyquaternium salt-11 was purchased from Shandong Jinyufeng New Materials Co., Ltd.

[0037] Preparation Example 1

[0038] The preparation method of modified polyquaternium salt-1 comprises the following steps:

[0039] (1) Add 10 g of 1H,1H-pentafluoropropanol, 5.5 g of acrylic acid, and 0.1 g of 85 wt% concentrated sulfuric acid to 100 ml of dichloromethane, heat to 75° C., stir for 7.5 h, and rotary evaporate to obtain the compound;

[0040] (2) 4 g of the compound obtained in step (1), 10 g of methacryloyloxyethyltrimethylammonium chloride and 0.1 g of azobisisobutyronitrile were added to anhydrous methanol and reacted at 65° C. During the reaction, the number average molecular weight was detected to obtain a modified polyquaternary ammonium salt-1 with a number average molecular weight of 889.

[0041] Preparation Example 2

[0042] The preparation method of modified polyquaternium salt-2 has the same specific steps as Preparation Example 1, except that the amount of acrylic acid added is 3.5 g.

[0043] Preparation Example 3

[0044] The preparation method of modified polyquaternium salt-3 has the same specific steps as Preparation Example 1, except that the amount of compound added is 8g.

[0045] Preparation Example 4

[0046] The preparation method of modified polyquaternium salt-4 has the same specific steps as those of Preparation Example 1, except that the number average molecular weight of the modified polyquaternium salt-4 is 1772.

[0047] Example 1

[0048] A method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint comprises the following steps:

[0049] S1. Add 1 g of sodium silicate, 3.1 g of magnesium nitride and 16.8 g of lithium chloride to 73 g of water, adjust the pH to 10 with NaOH at room temperature, and perform ultrasound for 55 min at an ultrasound power of 90 W to obtain a mixed solution;

[0050] S2. Add 2.7 g of modified polyquaternium salt-1 to 90 g of the mixed solution obtained in step S1, stir at 45° C. for 45 min, and then react at 120° C. for 15 h to obtain crystalline lithium magnesium silicate.

[0051] Example 2

[0052] A method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint comprises the following steps:

[0053] S1. Add 1 g of sodium silicate, 3 g of magnesium nitride and 16.7 g of lithium chloride to 70 g of water, adjust the pH to 9 with NaOH at room temperature, and perform ultrasound for 50 min at an ultrasound power of 100 W to obtain a mixed solution;

[0054] S2. Add 1.8 g of modified polyquaternium salt-1 to 90 g of the mixed solution obtained in step S1, stir at 40° C. for 60 min, and then react at 115° C. for 18 h to obtain crystalline lithium magnesium silicate.

[0055] Example 3

[0056] A method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint comprises the following steps:

[0057] S1. Add 1 g of sodium silicate, 3.2 g of magnesium nitride and 17 g of lithium chloride to 75 g of water, adjust the pH to 11 with NaOH at room temperature, and perform ultrasound for 60 min at an ultrasound power of 80 W to obtain a mixed solution;

[0058] S2. Add 3.84 g of modified polyquaternium salt-1 to 96 g of the mixed solution obtained in step S1, stir at ℃ for 45 min, and then react at 125℃ for 12 h to obtain crystalline lithium magnesium silicate.

[0059] Example 4

[0060] A crystalline lithium magnesium silicate for nano-scale colorful stone-like paint and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified polyquaternary ammonium salt-1 is replaced by modified polyquaternary ammonium salt-2.

[0061] Example 5

[0062] A crystalline lithium magnesium silicate for nano-scale colorful stone-like paint and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified polyquaternary ammonium salt-1 is replaced by modified polyquaternary ammonium salt-3.

[0063] Example 6

[0064] A crystalline lithium magnesium silicate for nano-scale colorful stone-like paint and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified polyquaternary ammonium salt-1 is replaced by modified polyquaternary ammonium salt-4.

[0065] Example 7

[0066] A crystalline lithium magnesium silicate for nano-scale colorful stone-like paint and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the amount of modified polyquaternary ammonium salt-1 added in step S2 is 5.4 g.

[0067] Comparative Example 1

[0068] A crystalline lithium magnesium silicate for nano-scale colorful stone-like paint and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of modified polyquaternium salt-1 is replaced by polyquaternium salt-11.

[0069] Performance Testing

[0070] The lithium magnesium silicate prepared in each embodiment and comparative example was added into water to prepare a 2 wt % solution, stirred at 300 rpm for 5 h, and allowed to stand for 24 h before being tested for viscosity and thixotropy at 25° C. using a rheometer, and for transmittance using a transmittance meter.

[0071] The speed test results are shown in Table 1.

[0072] Table 1

[0073] Group Viscosity(cP) Thixotropic value Light transmittance (%) Example 1 94.6 11.9 99.4 Example 2 94.1 11.2 99.0 Example 3 94.2 11.3 99.1 Example 4 93.5 10.8 99.2 Example 5 92.6 9.2 99.0 Example 6 93.1 9.5 98.1 Example 7 92.2 9.3 99.0 Comparative Example 1 87.5 10.7 89.1

[0074] By comparing the experimental data of Examples 1-3 in Table 1, it can be seen that the crystalline lithium magnesium silicate for nano-scale colorful imitation stone paint prepared by the preparation method has suitable viscosity, thixotropy and transmittance; compared with Example 1, Example 4 shows that the change in the ratio of 1H, 1H-pentafluoropropanol to acrylic acid in the modified polyquaternium salt-2 may increase the water solubility of the lithium magnesium silicate, and reduce both the viscosity and thixotropy; compared with Example 1, Example 5 shows that the change in the ratio of the compound to methacryloyloxyethyl trimethylammonium chloride in the modified polyquaternium salt-3 may result in the obtained The surface tension of lithium magnesium silicate is too low when used, and the viscosity and thixotropy are both reduced; it can be seen from the comparison between Example 6 and the example that the molecular weight of the modified polyquaternary ammonium salt increases, and it may be difficult to enter the interlayer, and the various properties of the obtained lithium magnesium silicate are all reduced; it can be seen from the comparison between Example 7 and Example 1 that the addition amount of the modified polyquaternary ammonium salt is changed, which may cause the ion exchange amount of the quaternary ammonium salt cation to change, resulting in a decrease in the viscosity and thixotropy of the lithium magnesium silicate; it can be seen from the comparison between Comparative Example 1 and Example 1 that the various properties of the prepared lithium magnesium silicate using commercially available polyquaternary ammonium salt are all reduced.

[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint, characterized in that: The following steps are involved: S1. Add a silicon-containing compound, a magnesium-containing compound and a lithium-containing compound into water, adjust the pH to 9-11 with NaOH at room temperature, and perform ultrasound for 50-60 min at an ultrasound power of 80-100 W to obtain a mixed solution; S2. Add modified polyquaternary ammonium salt to the mixed solution obtained in step S1, stir at 40-50° C. for 30-60 min, and then react at 115-125° C. to obtain crystalline lithium magnesium silicate.

2. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The silicon-containing compound is any one or more of sodium silicate, silicic acid and silicon dioxide.

3. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The magnesium-containing compound is any one or more of magnesium nitride, magnesium chloride, magnesium hydroxide, magnesium oxide, and magnesium acetate.

4. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The lithium-containing compound is any one or more of lithium chloride, lithium acetate and lithium carbonate.

5. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The mass ratio of the silicon-containing compound, the magnesium-containing compound, the lithium-containing compound and water is 1:(3-3.2):(16.7-17):(70-75).

6. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The preparation method of the modified polyquaternary ammonium salt comprises the following steps: (1) Add 1H,1H-pentafluoropropanol, acrylic acid and concentrated sulfuric acid to dichloromethane, heat to 70-80° C., stir for 7-8 hours, and rotary evaporate to obtain the compound; (2) adding the compound obtained in step (1), methacryloyloxyethyl trimethyl ammonium chloride and azobisisobutyronitrile to methanol, reacting at 60-70° C., detecting the number average molecular weight during the reaction, and obtaining a modified polyquaternary ammonium salt having a number average molecular weight of 680-940.

7. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 6, characterized in that: The mass ratio of the 1H,1H-pentafluoropropanol to acrylic acid is 1:(0.5-0.6).

8. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 6, characterized in that: The mass ratio of the compound in step (2) to methacryloyloxyethyltrimethylammonium chloride is (0.4-0.6):

1.

9. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The amount of the modified polyquaternary ammonium salt added in step S2 is 2-4% of the total mass of the silicon-containing compound, the magnesium-containing compound, the lithium-containing compound and water.

10. The method for preparing crystalline lithium magnesium silicate for nano-scale colorful stone-like paint according to claim 1, characterized in that: The reaction time in step S2 is 12-18 hours.

Citation Information

Patent Citations

  • A kind of hydrothermal synthesis method of nanoscale magnesium lithium silicate with high light transmittance

    CN105800626B

  • A high light transmittance and easy-dispersing method for synthesizing lithium magnesium silicate by high temperature solid phase

    CN106946263B